AESTHETICS OF ISLAMIC RHETORIC: AN EXAMINATION OF AS-SAJA’ AS A BUILDER OF LINGUISTIC BEAUTY IN THE BOOK NURUL WAHHAJ FI QISSOTI ISRA’ WAL MI’RAJ - Ilham Ahmad Wahyudin; Fadlil Yani Ainusyamsi; Mohamad Syasi (El-Tsaqafah : Jurnal Jurusan PBA, 2026)
Previous studies have generally examined the narrative of Isra' and Mi'raj from historical or jurisprudential perspectives, leaving a distinct research gap regarding the linguistic aesthetic dimensions of classical religious prose. Addressing this, this study aims to analyze the classification and rhetorical functions of the As-Saja’ (rhymed prose) stylistic device in the book Nurul Wahhāj fī Qiṣṣōti Isrā’ Wal Mi’rāj. This descriptive qualitative research employs a balaghah (rhetorical) approach focusing on 'Ilm al-Badi’, utilizing content analysis on the primary manuscript. The results identified 141 forms of As-Saja’, comprising Mutharraf (77 data), Mutawazi (56 data), and a minor portion of Murashsha’ (8 data). The dominance of Mutharraf and Mutawazi demonstrates that the author integrated rhyme as a systematic rhetorical strategy, not merely as a decorative ornament. In conclusion, As-Saja’ crucially functions to guide reading intonation, reinforce the retention of religious messages, and establish phonetic cohesion that optimizes the spiritual impact on readers